Über Natur und Mensch im brasilianischen Amazonasgebiet - Sioli, Harald (ERDKUNDE, 1956)
The aim of this paper is to be a sequel to and to enlarge upon the paper, ,,Die Amazonasniederung als harmonischer Organismus (the Amazon lowland as a harmonic organism), read by Hans Bluntschli almost . 40 years ago, a paper which has become in the meantime a classic description of the very essence of Amazonia. After dividing Brazil into three fairly uniform regions, one of which is Amazonia, the author then deals with its geological structure since it serves as a key to the understanding of many of the distinctive features of the nature Qf this region. A cross section through lower Amazonia is used to illustrate the present geomorphology of this region and also the meaning of the terms varzea, igapo and terre firme. Based on the most recent data available a climatic subdivision of Amazonia is given and the varzea campos of the lower Amazon are viewed in relationship to it. To explain the existence of the campos of the terre firme, edaphic factors and man's activity are taken into account in addition to the climate. A further section deals with the hydrological qualities and the riverside zones of the Amazonian whitewater, clearwater and blackwater rivers. In this context special reference is made to the peculiar unproportionately large estuaries and the typical river lakes of lower Amazonia, and their origin is explained by postglacial eustatic rise of the sea level and vertical earth movements. Finally the relationships between man and nature in Amazonia are· investigated and an account is given of their development so far. In conclusion the author considers what course the planned application of modern technology within and against nature in Amazonia will take and what its consequences will be.